2013
DOI: 10.1007/s11845-013-0980-4
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of tuberculous meningitis by an indirect ELISA protocol based on the detection of the antigen ESAT-6 in cerebrospinal fluid

Abstract: BackgroundEarly diagnosis of tuberculous meningitis (TBM) is still a challenge; the present study aimed to establish a method of detecting the antigen early secreted antigenic target 6 (ESAT-6) in cerebrospinal fluid (CSF) by an indirect enzyme-linked immunosorbance assay (ELISA) protocol and to study the value of detecting ESAT-6 in CSF in the early diagnosis of TBM.MethodsAn indirect ELISA protocol was used, employing a monoclonal antibody (mAb) against ESAT-6, which was used to demonstrate ESAT-6 in the CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
0
15
0
3
Order By: Relevance
“…Tuberculosis antigen cocktail rapid ICT :60-5 TB antigen cocktail rapid ICT from CSF specimens had a sensitivity of 83.3% and specificity of 68.5%. Song et al 16 reported that the sensitivity TB antigen ESAT-6 from CSF was 88% and the specificity was 92%. In Kashyap et al 17 sensitivity of TB antigen ESAT-6 was 80% and the specificity was 94%.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis antigen cocktail rapid ICT :60-5 TB antigen cocktail rapid ICT from CSF specimens had a sensitivity of 83.3% and specificity of 68.5%. Song et al 16 reported that the sensitivity TB antigen ESAT-6 from CSF was 88% and the specificity was 92%. In Kashyap et al 17 sensitivity of TB antigen ESAT-6 was 80% and the specificity was 94%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently several reports revealed potential application of detection of M. tuberculosis −specific antigens in CSF as rapid diagnosis of tuberculosis meningitis 39, 40 . The level of M. tuberculosis Early Secreted Antigenic Target 6 [ESAT-6] was associated with clinical severity, and may be used for the prognosis of tuberculosis meningitis 41, 42 .…”
Section: Conventional Microbiology Methodsmentioning
confidence: 99%
“…7,8 Hasil pemeriksaan mikroskopik BTA yang baik sangatlah dipengaruhi oleh kualitas bahan pemeriksaan, ketebalan hapusan dan lamanya dekolorisasi, jenis kontras pewarnaan yang digunakan, dan personil laboratorium yang terlatih. Terdapat organisme non-mycobacterial yang dapat memperlihatkan gambaran seperti BTA pada pemeriksaan mikroskopik BTA, yaitu Rhodococcus, Nocardia, Legionella micdadei, kista Cryptosporodium, Isospora, Cyclospora, dan spora Microsporidium.…”
Section: Pendahuluanunclassified
“…Bahan pemeriksaan yang dapat dipakai adalah sputum, serum, urine, dan cairan tubuh lain. [6][7][8] Saat ini terdapat pemeriksaan imunoserologi untuk mendeteksi cocktail antigen TB dengan menggunakan metode rapid immunochromatography (ICT).…”
Section: Pendahuluanunclassified